PEMANFAATAN POTENSI ALAMI SEBAGAI ANTIOKSIDAN - Happy, Terza Aflika; Septiani, Linda; Graharti, Risti; Andrifianie, Femmy (Medula, 2025)
Indonesia is one of the world’s most biodiverse countries and possesses a vast potential of medicinal plants as natural therapeutic resources. Many medicinal plants traditionally used by local communities are known to contain secondary metabolites with antioxidant properties. Antioxidants play an essential role in preventing oxidative stress associated with degenerative and infectious diseases. This article aims to review the potential of secondary metabolite compounds from Indonesian medicinal plants as antioxidant agents based on previous studies. This study was conducted using a literature review method by analyzing relevant national and international scientific publications. The results indicate that various medicinal plants, including sweet potato leaves, green tea, roselle, celery, and Peperomia pellucida, contain polyphenolic compounds such as flavonoids, tannins, and phenols, as well as other secondary metabolites including alkaloids, saponins, terpenoids, quinones, coumarins, and anthocyanins. These compounds exhibit antioxidant activity through free radical scavenging, hydrogen atom donation, and inhibition of lipid peroxidation processes. In conclusion, Indonesian medicinal plants demonstrate significant potential as natural sources of antioxidants and offer promising prospects for further development in pharmaceutical and health applications, particularly as raw materials for phytopharmaceutical products and supportive therapies.